2020
DOI: 10.1007/s10198-020-01159-y
|View full text |Cite
|
Sign up to set email alerts
|

Early cost-utility analysis of tissue-engineered heart valves compared to bioprostheses in the aortic position in elderly patients

Abstract: Objectives Aortic valve disease is the most frequent indication for heart valve replacement with the highest prevalence in elderly. Tissue-engineered heart valves (TEHV) are foreseen to have important advantages over currently used bioprosthetic heart valve substitutes, most importantly reducing valve degeneration with subsequent reduction of re-intervention. We performed early Health Technology Assessment of hypothetical TEHV in elderly patients (≥ 70 years) requiring surgical (SAVR) or transcatheter aortic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Due to limited durability of bioprostheses, repeat procedures (re-SAVR or valve-invalve TAVR and TAVR-in-TAVR) are inevitable for young adults throughout their life, so that the initially attractive cost-effectiveness of bio-SAVR may be diminished by the costs incurred for readmission, reintervention, and new prostheses needed by the patient. It has been demonstrated that even in elderly patients, decellularized homografts are more costeffective than SAVR and TAVR due to reduced adverse events rates [54]. Also, being sold at a higher price than bioprostheses, decellularized homografts remain not only cost-effective, but, most importantly, demonstrate a quality-of-life gain for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited durability of bioprostheses, repeat procedures (re-SAVR or valve-invalve TAVR and TAVR-in-TAVR) are inevitable for young adults throughout their life, so that the initially attractive cost-effectiveness of bio-SAVR may be diminished by the costs incurred for readmission, reintervention, and new prostheses needed by the patient. It has been demonstrated that even in elderly patients, decellularized homografts are more costeffective than SAVR and TAVR due to reduced adverse events rates [54]. Also, being sold at a higher price than bioprostheses, decellularized homografts remain not only cost-effective, but, most importantly, demonstrate a quality-of-life gain for the patients.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 50 , 69 By contrast, TEHVs are living tissues having regenerative capacity, which thereby have the potential to become superior valve replacements compared to contemporary valve replacements. 42 , 43 To enable this transition, the regeneration and adaptation of TEHVs should be understood and well controlled such that proper, ideally native-like, valve function is established during tissue development and maintained over long periods through tissue adaptation and repair.…”
Section: Illustration 1: Tissue Engineered Heart Valves (Tehvs)mentioning
confidence: 99%